What Does Leaders' Character Add to Transformational Leadership?. Issue 3 (3rd April 2017) - Liborius, Patrick
ABSTRACT: The influence of leaders' character (e.g., integrity, humility/forgiveness) has rarely been examined in leadership research. The current investigation focused on the impact of integrity and humility/forgiveness on both followers' perceptions of leaders' worthiness of being followed (WBF) and stress. Results from a scenario experiment ( n = 347) and a field study ( n = 110) indicated that these aspects incrementally predict WBF above and beyond the impact of transformational leadership. Similar results were found concerning followers' stress with the exception of leader integrity in the field study. According to relative importance analyses, integrity and transformational leadership predict WBF equally well. The results have conceivable implications for human resources (personnel selection and development). Future research should examine additional outcome variables that are affected by certain leader characteristics as well as potential negative effects of the examined character aspects.